2020
DOI: 10.2147/cmar.s242464
|View full text |Cite
|
Sign up to set email alerts
|

<p>SP1-Induced Upregulation of lncRNA LINC00514 Promotes Tumor Proliferation and Metastasis in Osteosarcoma by Regulating miR-708</p>

Abstract: Background: Growing studies have suggested the dysregulation of long non-coding RNAs (lncRNAs) in several tumors, including osteosarcoma (OS). However, limited studies report metastasis-associated lncRNAs in OS. Our present study aimed to explore the roles of lncRNA LINC00514 (LINC00514) in OS. Materials and Methods: The LINC00514 expression was measured using qPCR assays in OS tissues and cell lines. The clinical significance of LINC00514 expression in OS patients was analyzed using chi-square test, Kaplan-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…LINC00514 was reported to be involved in the development and progression of neuroendocrine prostate cancer. Mi et al ( 38 ) found that the expression of LINC00514 was markedly upregulated in osteosarcoma tissues and cells, and high levels of LINC00514 were positively associated with advanced tumor stages, distant metastasis and reduced overall survival of patients. Another study on osteosarcoma confirmed that LINC00514 was upregulated in osteosarcoma tissues and cells, and an increased LINC00514 level was associated with tumor size, TNM stage and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LINC00514 was reported to be involved in the development and progression of neuroendocrine prostate cancer. Mi et al ( 38 ) found that the expression of LINC00514 was markedly upregulated in osteosarcoma tissues and cells, and high levels of LINC00514 were positively associated with advanced tumor stages, distant metastasis and reduced overall survival of patients. Another study on osteosarcoma confirmed that LINC00514 was upregulated in osteosarcoma tissues and cells, and an increased LINC00514 level was associated with tumor size, TNM stage and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al ( 18 ) verified that LINC00514 knockdown suppressed cell proliferation in vitro and in vivo , as well as colony formation, migration and invasion in osteosarcoma. LINC00514 functioned as a ceRNA by directly absorbing miR-708-5p, and consequently promoting cell proliferation ( 38 ). In addition, LINC00514 downregulation suppressed the proliferation, migration and invasion of papillary thyroid cancer cells, which was achieved by sponging miR-204-3p to increase the expression of cell division cycle 23 ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al [ 29 ] illustrated that LINC00514 enhanced osteosarcoma development by sponging miR-708/URGCP. Mi et al [ 30 ] also noted that SP1-influenced LINC00514 overexpression induced metastasis and growth by modulating miR-708 in osteosarcoma. Until now, the roles of LINC00514 in gastric tumor are undefined and need to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, researchers found that the expression of many lncRNAs was dysregulated in a variety of tumours, including gliomas and that the expression levels of some lncRNAs could be used as prognostic indicators (10,11). With further studies, researchers have found that lncRNAs can affect tumour progression by their involvement in a variety of cellular processes, such as proliferation, migration, invasion, autophagy, and epithelial-mesenchymal transition (EMT) (12)(13)(14). COX10 antisense RNA 1 (COX10-AS1) is a non-coding transcript located on chromosome 17 (14029292-14069458, complement).…”
Section: Introductionmentioning
confidence: 99%